1996
DOI: 10.1128/jvi.70.6.3844-3851.1996
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus E4 open reading frame 4 protein autoregulates E4 transcription by inhibiting E1A transactivation of the E4 promoter

Abstract: Here we show that the adenovirus early region 4 (E4) open reading frame 4 (ORF4) protein autoregulates its own transcription by inhibiting adenovirus E1A-induced activation of E4 transcription both in transient transfection experiments and during lytic virus growth. The inhibitory activity of E4-ORF4 was selective for E1A-CR3-dependent transactivation and had no effect on CR1 transactivation. The inhibitory activity of E4-ORF4 was relieved by okadaic acid treatment, which inhibits the cellular protein phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…While investigating the mechanisms underlying E4orf4-induced down-regulation of stimulated gene expression, we have found that the E4orf4 protein binds several cellular proteins, one of which has been identified as protein phosphatase 2A (PP2A) (26). We and others have further shown that the E4orf4-PP2A interaction plays a role in down-regulation of stimulated transcription (5,26).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…While investigating the mechanisms underlying E4orf4-induced down-regulation of stimulated gene expression, we have found that the E4orf4 protein binds several cellular proteins, one of which has been identified as protein phosphatase 2A (PP2A) (26). We and others have further shown that the E4orf4-PP2A interaction plays a role in down-regulation of stimulated transcription (5,26).…”
mentioning
confidence: 96%
“…It appears, therefore, that as E4orf4 accumulates, it causes AP-1 DNA binding to return to its basal levels. E4orf4 activities also result in hypophosphorylation of E1A and c-fos proteins (38), and as a consequence of the cumulative E4orf4 effects, its own promoter is down-regulated as well (5,59).…”
mentioning
confidence: 99%
“…The E4orf6 protein has also been reported to interact with the C-terminal regulatory domain of the p53 tumor suppressor, inhibiting p53-dependent transactivation and apoptosis (13,34). Another E4 protein, the E4orf4 protein, apparently associates with endogeneous phosphatase 2A, modulating the function of viral (e.g., E1A) and cellular transcription factors (4,28,35).…”
mentioning
confidence: 99%
“…Cells infected with Ad5.dl1014 demonstrate minimal adenoviral DNA replication [59]. The ability of E4orf4 to downregulate the activity of E1A proteins, either directly or via cellular intermediaries, causes the DNA replication defect when cells are infected in the absence of E4orf6 or E4orf3 by reducing the expression of viral genes dependent on the phosphorylation of the R289 residue of the E1A protein [60][61][62]. Decreased expression of these downstream viral genes would be expected to reduce systemic toxicity associated with dissemination of these vectors.…”
Section: Discussionmentioning
confidence: 99%